MAKNA ASPEKTUALITAS AFIKSASI DAN REDUPLIKASI PADA VERBA BAHASA BUGIS - Bungatang Bungatang (Universitas Negeri Makassar, 2017)
Abstract. Aspectuality meaning of affixation and reduplication in buginese verb. Aspectuality meaning can be exposed to Bugise language as a language that has the morphology. This research aims to disclose (1) the aspectuality meaning of affixation in Buginese verb, (2) the aspectuality meaning of reduplication in Buginese verb. The method of the research was descriptive qualitative. Data sources of the research are both written and spoken text. The data were collected with observation, (2) documentation, (3) and note taking. The research reveals that (1) the aspectuality meaning derived from the behavior of affixation of Buginese verb, i.e. (a) semelfactive meaning which its existence is characterized by prefix ta-D and tappa-D, (b) frequentative-intensive meaning which its existence is characterized by prefix si-D, and (c) habituative-intensive meaning which its existence is characterized by confiks pa-D-eng and (2) aspectuality meaning is derived from the behavior of reduplication of Buginese verb, i.e. habituative-intensive meaning which its existence is characterized by category ka-D+R, pa-D-eng+R, dan pa-D+R.